An exploratory study of project financing urban infrastructure - Magqaza, Ayanda (Research of GSB, 2018)
This research paper aims to explore the use of project finance to fund urban infrastructure in order to aid the development of affordable housing. This is due to the high rate of urbanisation in developing nations, leading to the challenge of providing adequate shelter and the requisite infrastructure. Although South Africa has been lauded for making observable strides in housing and infrastructure provision, infrastructure is still required. There is reluctance to bring private finance into infrastructure development in developing economies because full recovery of invested capital is not easy to achieve. Project finance is recommended to improve the rate of shelter provision as well as to catalyse the eradication of slums. Project finance was investigated through interviewing selected participants, based on their role in the infrastructure provision sector. The outcomes indicated that project finance is an appropriate tool due to its characteristics.